Opposition and Truth: Parmenides’ Enigmatic Way - Tarca, Luigi Vero (Peitho. Examina Antiqua, 2013)
In Parmenides’ B 8 37–41, we find a question that raises a difficult problem: how can Parmenides handle the opposition between “being and not” (i.e. being and not being) in the same way as the oppositions which characterize the mortals’ opinions? This question is especially relevant for answering the following theoretical question: how do we to treat the fundamental philosophical question of oppositions at large? To answer these question we need to reinterpret some major points of Parmenides’ thought: the second part of his poem, but also the identification of πέλειν and εἶναι in B 6 8, as well as other passages of the poem. But, above all, the question makes us introduce some distinctions within the concept of negation and, consequently, between difference and negation. This allows us to distinguish the affirmation of the truth of being from the negation of the negation of being (i.e. the negation of nonbeing). This distinction has a major philosophical relevance, as can be seen by referring it to such thinkers as Plato, Hegel and Heidegger.